2016
DOI: 10.1088/1758-5090/8/2/025003
|View full text |Cite
|
Sign up to set email alerts
|

Micro-precise spatiotemporal delivery system embedded in 3D printing for complex tissue regeneration

Abstract: Three dimensional (3D) printing has emerged as an efficient tool for tissue engineering and regenerative medicine, given its advantages for constructing custom-designed scaffolds with tunable microstructure/physical properties. Here we developed a micro-precise spatiotemporal delivery system embedded in 3D printed scaffolds. PLGA microspheres (μS) were encapsulated with growth factors (GFs) and then embedded inside PCL microfibers that constitute custom-designed 3D scaffolds. Given the substantial difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 28 publications
1
119
0
2
Order By: Relevance
“…High (1,000 ng/ml) and low (100 ng/ml) doses of CTGF and 10 mg of fast (75:25, lactic and glycolic acids) and slow (85:15) TGFβ3‐encapsulated PLGA μS were applied. A single dose PLGA μS was applied to all the groups as optimized from our previous works in order to focus on the effect of release. Then, the meniscus explants were placed on top of monolayer‐cultured P2–3 synovial MSCs at 80– 90% confluence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High (1,000 ng/ml) and low (100 ng/ml) doses of CTGF and 10 mg of fast (75:25, lactic and glycolic acids) and slow (85:15) TGFβ3‐encapsulated PLGA μS were applied. A single dose PLGA μS was applied to all the groups as optimized from our previous works in order to focus on the effect of release. Then, the meniscus explants were placed on top of monolayer‐cultured P2–3 synovial MSCs at 80– 90% confluence.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the meniscus explants were placed on top of monolayer‐cultured P2–3 synovial MSCs at 80– 90% confluence. Supplements for fibrogenic and chondrogenic differentiation were applied as described in our recent publication . At 8 weeks, fibrocartilaginous tissue integration was evaluated by H&E and Saf‐O staining.…”
Section: Methodsmentioning
confidence: 99%
“…When applied in vivo , 4-week TMJ disc explant samples displayed recovery of the defect site, being mechanically sound with a highly-organized fibrocartilage structure mirroring native tissue. (80) In a separate study, the authors also demonstrated that in addition to heterogeneous tissue formation after CTGF and TGF-β3 release, gene upregulation was highly dependent on the dose of growth factor used, with the 100mg microsphere/g scaffold dose yielded significantly increased collagen I and II and aggrecan expression than the 50mg/g dose. (81)…”
Section: Target Tissues and Applicationsmentioning
confidence: 97%
“…Tarafder et al showcased another multi-cartridge printing approach towards temporomandibular joint (TMJ) disc regeneration in which alternating strands of poly(ε-caprolactone) (PCL) were printed with poly(lactic-co-glycolic acid) (PLGA) microspheres containing either connective tissue growth factor (CTGF) or TGF-β3. (32) Other extrusion and inkjet techniques have utilized multi-printhead systems to great success for printing bioinks with distinct temperature, pneumatic pressure, and nozzle size requirements, such as the integrated tissue-organ printer system developed by Kang et al(33) Ultimately, single-printhead systems may be most suitable for the printing of bioinks with highly similar material compositions, while multi-printhead systems on the other hand will benefit from improvements to speed of printhead switching and the ability to maintain continuous printing when switching between bioinks with print conditions.…”
Section: Fabricating Spatiotemporal Growth Factor Patternsmentioning
confidence: 99%
“…Tarafder, et al in 2016 studied the use of micro-precise 3D printed spatiotemporal delivery systems embedded with PLGA microspheres and growth factors (Tarafder et al, 2016). Specifically, MSCs from either human bone marrow (100,000 cells/mL) or rabbit TMJ synovium (200,000 cells/mL) were seeded onto a 3D printed scaffold with a similar anatomical shape and contour to a native TMJ disc.…”
Section: Temporomandibular Joint Discmentioning
confidence: 99%